2001
DOI: 10.1007/s002770100375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prednisone and splenectomy in patients with idiopathic thrombocytopenic purpura: only splenectomy induces a complete remission

Abstract: Idiopathic thrombocytopenic purpura (ITP) is a heterogeneous disease, whereby it is unclear if and in which way prednisone and splenectomy affect the platelet kinetics leading to a complete remission. To determine the effects of prednisone and splenectomy on the mean platelet life (MPL) and platelet production, platelet kinetic studies with Indium-111 tropolonate-labeled autologous platelets were performed in patients with ITP ( n=41). In 17 patients platelet kinetic studies were performed before and during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Previous studies have shown that prednisone improves the platelet count in ITP primarily by increasing platelet production [9,10]. The present findings are consistent with these results by showing that ITP patients with the lowest PPR are the most likely to respond to prednisone in the long term.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that prednisone improves the platelet count in ITP primarily by increasing platelet production [9,10]. The present findings are consistent with these results by showing that ITP patients with the lowest PPR are the most likely to respond to prednisone in the long term.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with these findings are platelet kinetic studies using radioactive indium ( 111 In), which have shown that splenectomy improves the platelet counts predominantly by increasing platelet survival [9,10]. In these studies [9,10], prednisone primarily affected the platelet production, which contradicted earlier radiolabeled platelet studies using chromium-51 ( 51 Cr), suggesting that successful response to prednisone was caused by an increase in platelet survival [11]. In the present study, we investigated the predictive value of thrombokinetic and clinical parameters in 75 adult patients with severe ITP.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, there are many reports about a reduced PPR in a subgroup (30% to 50%) of ITP patients. 4,5,6,39,40 Experiments in which thrombokinetic studies were repeated after splenectomy and prednisone treatment showed that both forms of treatment can induce a distinct increase in PPR, 41 indicating that the release of platelets to the circulation (ie, PPR) in active ITP is relatively depressed, perhaps due to the action of autoantibodies directed against megakaryocytes.Besides the results of reduced platelet production in platelet kinetic studies, the present study gives additional evidence for reduced platelet production by injured megakaryocytes. In a recent study 13 we observed a significant inverse correlation between the PPR and the glycocalicin index (GCI) in ITP patients.…”
mentioning
confidence: 99%
“…Even though major disadvantages of splenectomy include rare but serious postoperative infections (5), the financial burden, and perioperative risks, splenectomy seemed similar to steroid therapy in that both therapies are palliative rather than curative. Complete remission of the disease, defined by platelet count, mean platelet life, and platelet production, is reportedly obtained only after splenectomy and not after prednisone treatment (6). The laparoscopic approach was selected because this induces less damageto abdominal muscle than the laparotomy approach.…”
mentioning
confidence: 99%